(untitled) (Medical Forum Monthly, 2022)
Objective: To study the effect of aerobic exercise on histomorphometery of bone. Study Design: Experimental study Place and Duration of Study: This study was conducted in Ziauddin University, Karachi from February 2021 to April 2021 for a period of 8 weeks. Materials and Methods: The study samples were 12 male Sprague Dawly Rats (SD) weighing 200-300gms, divided into two groups; 6 assigned to the experimental group and 6 to the control group. Data was collected through Maze Engineers Multilane rat treadmill and Nikon INTENSELIGHT C-HGFI. Data analyzation was done using SPSS version 25. Skewness and Kurtosis tests were applied in order to check the normality of data. Independent T-test was applied between both the groups to determine mean values on the similar outcome measures and a p-value of <0.05 was considered to be significant. Results: The study observed a statistically significant increase in Haversian canal diameter, increase in area in the post-exercise group of rats, an increase in the number of lamellae per osteon with exercise and a greater average osteon area in the exercise group. However, a statistically significant difference could not be observed in the number of osteon per high power field (HPF) between the two groups. Conclusion: Findings of this study suggest that weight-bearing exercises such as treadmill running help increasing the density and strength of the cortical bones, amplifying their morphology. Thus, the study concluded that seven weeks of aerobic training results in improved bone morphology parameters.